2006
DOI: 10.1148/radiol.2382041441
|View full text |Cite
|
Sign up to set email alerts
|

An Augmented Reality System for MR Image–guided Needle Biopsy: Initial Results in a Swine Model

Abstract: Biopsy procedures performed with a combination of a closed-bore MR system and an AR system are feasible and accurate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 42 publications
2
72
0
3
Order By: Relevance
“…Follow-on work by Rosenthal and colleagues [37] showed that a skilled surgeon could complete biopsies more accurately with the AR system than with standard imaging. Wacker and colleagues [46] demonstrated and evaluated a needle biopsy system using a swine model. Blum, Sielhorst, and Navab [8] used AR to visualize the path through which a trainee manipulates an obstetric forceps relative to the trajectory followed by an expert.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Follow-on work by Rosenthal and colleagues [37] showed that a skilled surgeon could complete biopsies more accurately with the AR system than with standard imaging. Wacker and colleagues [46] demonstrated and evaluated a needle biopsy system using a swine model. Blum, Sielhorst, and Navab [8] used AR to visualize the path through which a trainee manipulates an obstetric forceps relative to the trajectory followed by an expert.…”
Section: Related Workmentioning
confidence: 99%
“…In contrast, we provide continuous prescriptive feedback for alignment tasks. The needle biopsy systems [41,37,46] display virtual representations of tracked biopsy needles within the patient's body. These systems differ from ours in that they intentionally do not provide explicit prescriptive instructions to the user, but instead rely on the skilled surgeon to make her own decisions based on the AR visualization.…”
Section: Related Workmentioning
confidence: 99%
“…The most widely used form, digital subtraction angiography, subtracts the corresponding pixels in a recent radiocontrast angiogram from superposed live X-Ray fluoroscopy [1]. Roadmaps derived from disparate imaging modalities can be combined in several ways, ranging from computed tomography (CT) [2,3] or MRI-derived [4,5] myocardial images overlaid onto electro-anatomic maps, or magnetic resonance images combined with live "heads-up" optical surgical headsets [6].…”
Section: Introductionmentioning
confidence: 99%
“…Birkfellner et al [2] designed and developed the VarioscopeAR, an augmented reality head mounted operation microscope, for maxillofacial surgery. Sauer et al [3] use a stereoscopic video-see through head mounted display to visualize three dimensional imaging data for various domains in interventional radiology and surgery [4].…”
Section: Introductionmentioning
confidence: 99%